Online Behavior and Loyalty Program Participation-parameters Influencing the Acceptance of Contactless Payment Devices - Fiedler, Martin; Öztüren, Ali (Maxwell Scientific Organization, 2014)
This study explores the central perceptions of consumers influencing the decision to use contactless payment instruments. Aim is to define a customer core group narrowed down by several variables and to find a basis for a purposeful communication of advantages of the new payment process, as investment into this technology bears the risk of total loss if the customer group is declining acceptance and the image of a company might be excessively damaged. External variables in context with the usage of social online media and participation in customer loyalty programs have been selected to clarify possible impact. These factors offer comprehensive explanation and help interpreting mechanisms within the decision making process for acceptance of the payment technology. Data were collected in a survey with n = 1,294 customers in a major city in Northern Germany. Results are displayed in a technology acceptance model, using structural equation modelling and regression analysis. The study is not limited on mobile payment instruments in the traditional context respectively involving a mobile phone. On the contrary this analysis is made on the belief that any device can be enabled for contactless payment processes, such as traditional items like credit or debit cards. Customers shopping online have a higher perceived usefulness an customers participating in loyalty programs tend to understand the argument of the ease of use of the technology more than their counterparts.
The file in this item is the publisher version (published version) of the article.
Keywords: Contactless Payment; Credit Card; Mobile Payment; RFID; TAM; Technology Acceptance